Handbook of Communication for Development and Social Change - Servaes, Jan 1952-; Servaes, Jan 1952- (Springer, 2026)
This handbook provides a single reference resource for communication for development and social change. Increasingly, one considers communication to be crucial to effectively tackle the major problems of today. Hence, the question being addressed in this handbook is, is there a right communication strategy? Perspectives on sustainability, participation, and culture in communication have changed over time in line with the evolution of development approaches and trends, and in response to the need for effective applications of communication methods and tools to new issues and priorities. Divided into prominent themes comprising relevant chapters written by experts in the field and reviewed by renowned editors, the book addresses topics where communication and social change converge in both theory and praxis. Specific concerns and issues include food security, climate change, poverty reduction, health, equity and gender, sustainable development goals, and information and communication technologies (ICTs). The book shows how communication is essential at all levels of society. It helps readers understand the processes that underlie attitude change and decision-making and the work uses powerful models and methods to explain the processes that lead to sustainable development and social change. This is essential reading for academics and practitioners, students and policy makers alike
Keywords: Development Communication; Communication; Social change; Environmental sciences; Economic development; Communication in economic development.; Communication in the environmental sciences.